Dynamics of the main plasma parameters during spontaneous transition into the mode of improved confinement in torsatron U-3M - Pashnev, V.K.; Sorokovoy, E.L.; Petrushenya, A.A.; Mironov, Yu.K.; Konovalov, V.G.; Shapoval, A.N.; Slavnyj, A.S.; Dreval, M.B.; Pugovkin, A.P. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The work [1] contains discussion about the changes in plasma energy content and energy lifetime during the transition into the mode of improved confinement at RF-heating in torsatron U-3M in range of rare collision frequencies of plasma particles. It was proved, that both energy content of plasma volume and energy lifetime increase as a result of transition into the mode of improved confinement. This increase is almost in 2 times. Temporal behavior of such plasma parameters as ion and electron temperature, plasma density and average charge state of plasma ions in the modes with improved confinement are discussed and reviewed in this work.